2015
DOI: 10.1155/2015/874906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Variations in Maize Seedlings Exposed to Electric Field Based on Protein and DNA Markers

Abstract: The current study analyzed proteins and nuclear DNA of electric fields (ELF) exposed and nonexposed maize seedlings for different exposure periods using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), isozymes, random amplified polymorphic DNA (RAPD), and comet assay, respectively. SDS-PAGE analysis revealed total of 46 polypeptides bands with different molecular weights ranging from 186.20 to 36.00 KDa. It generated distinctive polymorphism value of 84.62%. Leucine-aminopeptidase, peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Following genotoxicity studies, protein profiling was performed as a vital parameter that can elucidate translational ramifications of environmental mutagens at the molecular level (Al-Huqail and Abdelhaliem, 2015; Dogan et al, 2016). DNA strand breaks and variations in DNA coding sequences cause divergence in primary conformation of proteins (Al-Huqail and Abdelhaliem, 2015). Such gene alterations resulting in altered protein expression can be best observed by SDS-PAGE, an established technique for the detection of alterations in protein profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Following genotoxicity studies, protein profiling was performed as a vital parameter that can elucidate translational ramifications of environmental mutagens at the molecular level (Al-Huqail and Abdelhaliem, 2015; Dogan et al, 2016). DNA strand breaks and variations in DNA coding sequences cause divergence in primary conformation of proteins (Al-Huqail and Abdelhaliem, 2015). Such gene alterations resulting in altered protein expression can be best observed by SDS-PAGE, an established technique for the detection of alterations in protein profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The electrophoretic banding pattern of proteins observed in the current study provides information concerning the regulatory systems of structural genes that control the biosynthetic pathways of proteins in response to genotoxic environmental stress (Abdelhaliem et al, 2013;Al-Huqail and Abdelhaliem, 2015). Studies using SDS-PAGE analysis have shown that qualitative and quantitative changes in electrophoretic protein banding patterns occur in wheat grains exposed to CO 2 and O 3 , on their own or in combination, compared to control samples under irrigated and non-irrigated conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Changes in the intensity of polypeptide bands may result from changes in the expression of regulatory genes or from gene mutations in the regulatory system, which modulate or increase the rate of transcription of a particular structural gene, as suggested by Abdelhaliem et al (2013) and Al-Huqail and Abdelhaliem (2015). The alterations observed in protein banding pattern induced by variable levels of oxidative stress produced by O 3 and CO 2 treatments reflects the transcriptional events, which may alter plant metabolism by modifying proteins and enhancing their susceptibility to "proteolytic degradation" leading to oxidative protein lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the polypeptide band sizes might be attributed to the occurrence of point mutations in the relevant genes, creating stop codons that lead to production of longer or shorter polypeptide chains 25 . The intensity of polypeptide bands varied among treated and untreated samples (as shown in the Supplementary File: Tables 1-S to 7-S) and this might be due to changes in the regulatory gene expression, which modulated the rate of transcription of a specific structural protein, an observation consolidated by other researchers 26 . The appearance of unique bands, as a result of CAS treatment, may be interpreted by the fragmentation of polypeptide bands due to gene replication following a frameshift mutation.…”
Section: Discussionmentioning
confidence: 72%